The Mata Golo Ritual in the Culture of Ngada of Central Flores and Its Challenges for Catholic Theology - Wilfridus Ferdinandus Beo Dey; Albertus Magnus Rea (Ledalero Institute of Philosophy and Creative Technology (IFTK Ledalero), Indonesia, 2025)
The theology and death rituals of the Catholic Church are challenged by the concept of the Mata Golo ritual in the Ngada culture of Central Flores. Although the majority of the Ngada people are Catholic, their understanding and practices surrounding death especially in cases of unnatural death (Mata Golo), such as suicide, accidents, or murder are significantly different from the theology and rituals of the Catholic Church. In such cases, the bodies of the deceased are not treated according to the Catholic rites, but instead are fully honoured through the traditional Mata Golo rituals. This research, conducted between December 2023 and January 2024, aims to assess the influence of Catholic theology and death rituals when confronted with the Mata Golo concept and practices. A qualitative approach was employed, utilizing literature reviews, observation, and interviews. To interpret these dynamics within the framework of contextual theology, the researcher began with a receptive process by listening to and engaging with the local culture, followed by theological dialogue and synthesis. The theological model applied in this study is based on the concept of counter-culture. The findings indicate that, in the face of Mata Golo events and rituals, the Catholic teachings and rites concerning death have a limited influence. The Church's position, particularly regarding Catholic theology and death rituals, appears significantly weakened in comparison to the strong influence of the Mata Golo tradition. Therefore, a model of encounter is needed as a form of critical engagement with the Mata Golo ritual practice. This study is expected to contribute to the body of knowledge in the fields of contextual theology, sociology of religion, and anthropology of religion.